Fabrication and characterization of graphene hydrogel via hydrothermal approach as a scaffold for preliminary study of cell growth - Lim, H.; Huang, N.; Lim, S.; Harrison, I.; Chia, C. (Dove Medical Press, 2011)
BACKGROUND: